2015
DOI: 10.4236/as.2015.65053
|View full text |Cite
|
Sign up to set email alerts
|

Biological Management of Damping-Off, Buckeye Rot and Fusarial Wilt of Tomato (cv. Solan Lalima) under Mid-Hill Conditions of Himachal Pradesh

Abstract: Disease management is often complicated by the presence of multiple types of pathogens; in an organic system, it is appropriate to develop disease control strategies. The available literature so far reflects that the management of important disease of tomato is through the integrated approaches and very few organic approaches have been tried with various degree of success. Boiopriming of seeds with biocontrol agents (Trichoderma viridae, Trichoderma harzianum and Pseudomonas fluorescens) in combination with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Previous studies have showed that the biopriming of tomato seeds with Trichoderma isolates (T. viride and T. harzianum) and bacterial antagonist P. fluorescens in combination with FYM 200 q/ha + Azospirillum + PSB + T. harzianum (4 kg/ha each) recorded highest seed germination (93.1%) with a vigor index of 953.33. This treatment also showed 45.6% and 58.0% reduction of pre and post emergence damping off, respectively, over control (Thakur and Tripathi 2015). Similar findings of effectiveness of biocontrol agents against disease, improvement in seedling vigor, seedling emergence were recorded in cauliflower (Sharma and Sain 2005), capsicum and tomato (Pietr et al 2002).…”
Section: Efficacy Of Consortia Against Disease and Other Growth Parameters In Nurserysupporting
confidence: 63%
“…Previous studies have showed that the biopriming of tomato seeds with Trichoderma isolates (T. viride and T. harzianum) and bacterial antagonist P. fluorescens in combination with FYM 200 q/ha + Azospirillum + PSB + T. harzianum (4 kg/ha each) recorded highest seed germination (93.1%) with a vigor index of 953.33. This treatment also showed 45.6% and 58.0% reduction of pre and post emergence damping off, respectively, over control (Thakur and Tripathi 2015). Similar findings of effectiveness of biocontrol agents against disease, improvement in seedling vigor, seedling emergence were recorded in cauliflower (Sharma and Sain 2005), capsicum and tomato (Pietr et al 2002).…”
Section: Efficacy Of Consortia Against Disease and Other Growth Parameters In Nurserysupporting
confidence: 63%
“…However, issues related to human and soil health, environmental hazards, and disturbed ecosystem [6,7,8,9] pressurized the agriculturists to switch over the plant protection measures towards the safer and eco-friendly approaches [10]. Biological control agents could be an ideal approach for diseases management [11,12,13] as they have no chance to get into the food chain and hence safe to human beings, animals, and plants [14].…”
Section: Introductionmentioning
confidence: 99%
“…Damping-off disease prefers the immature host tissue and rapidly kills huge numbers of seedlings in the nursery beds (Thakur and Tripathi, 2015). Pythium spp.…”
Section: Introductionmentioning
confidence: 99%